Contemporary guided bone regeneration therapy for unaesthetic anterior peri-implantitis case - Benso Sulijaya; Sandra Olivia Kuswandani; Yuniarti Soeroso (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Dental implant is one of an alternative solutions reconstruction therapy for missing teeth. Complication of dental implant could occurs and leading to implant failure. In order to restore the complication, surgical treatment with guided bone regeneration (GBR) is indicated. The potential use of bone substitutes is widely known to be able to regenerate the bone surrounding the implant and maintain bone volume. Purpose: The study aimed to demonstrate the effectiveness of implant-bone fully coverage by using sandwich technique of biphasic calcium phosphate (BCP) and demineralized freeze-dried bone allografts (DFDBA) bone substitutes combined with collagen resorbable membrane. Case: A 24-year-old male came with diagnosis of peri-implantitis on implant #11. Clinical finding indicated that implant thread was exposed on the labial aspect. Case management: After initial therapy including oral hygiene improvement performed, an operator did a contemporary GBR to correct the defect. Bone graft materials used were 40% β-tri calcium phosphate (β-TCP)-60% hydroxyapatite (HA) on the outer layer and DFDBA on the inner layer of the defect. Resorbable collagen membrane was used to cover the graft. Conclusion: GBR with sandwich technique could serve as one of the treatment choices for correcting an exposed anterior implant that would enhance the successful aesthetic outcome.